Rwandan coffee used to make beer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
A London brewery has started producing beer brewed from Rwandan coffee beans. The beer, which has a 4% alcohol content, is targeted at adult drinkers as a cappuccino drink or digestif...